Characteristics of the Blasted Muck and the Loader's Productivity - S. P. Singh; R. Narendrula (International Society of Explosives Engineers, 2005)
The productivity of a loading machine is affected by several factors. One of the most significant is the characteristic of the muck being loaded. A study was conducted to examine the effects of the looseness, angle of repose, size distribution and moisture content of the blasted material on the efficiency of the loading machine. The study was conducted in the following stages: (a) controlled experiments in the lab, (b) tests with loader simulator and (c) field work in an operating mine. It was found that looseness (%void) in the muck increases with the increase in the value of the mean particle size and index of uniformity of the fragmented rock. Looseness and angle of repose affect the fill factor and the digging cycle time of a loader and in turn the productivity of the equipment. Moisture content affects the angle of repose as well as the stickiness of the material to the loader’s bucket. It was observed that the angle of repose increased with the increase in the mean particle size and the moisture content of the muck. It was also found that the bucket full factor and rate of scooping decrease with the increase in the values of mean particle size and index of uniformity. This was also conformed during fieldwork that bucket fill factor decreases with the increase in the mean particle size as well as the index of uniformity.